Analisis Faktor Penentu Preferensi Konsumen Dalam Berbelanja Ke Pasar Tradisional Di Kota Denpasar: Analisis Faktor - Ayuningsasi, Anak Agung Ketut (Jurnal Ekonomi Kuantitatif Terapan, 2013)
The rapid modernization of current concern in consumer preferences could shift from traditional markets to modern shopping center. Implementation of the revitalization of traditional market in Denpasar, is not expected to change in the preferences of consumers shopping at traditional markets. This study aims to construct the variables that determine consumer preferences in shopping to traditional markets. To solve these problems, this study performed a factor analysis to form a variable determinant of consumer preferences. Based on the results of the factor analysis found that the variable determinant of consumer preferences formed of indicator frequency of visits to traditional markets before the revitalization, frequency of visits to traditional markets after the revitalization, and the level of preference of respondents to the traditional market.
Keywords: Traditional Market; Consumer Preference; Market Revitalization; factor analysis